Exploring oral interaction in a North Lebanon primary school - Khawaja, Pierre (Beirut University of Balamand. Faculty of Arts and Social Sciences, 2009)
Ellis (1994) stated that interaction in a second or foreign language classroom is important because it provides opportunities for development and practice of language skills. In addition, interaction is considered necessary for negotiation of meaning, the basis for second language acquisition. My experience in learning English in a local English school revealed that the standard use of oral interaction was generally low. Now that I am a teacher and learning about theories in education, I returned to my school and investigated oral interaction in the English classes. The research project highlighted current thinking on how languages are learned drawing on different learning theories. I investigated what kinds of oral interaction took place in grade eight. I used observations, interviews and questionnaires to collect the data. This data helped me to understand what opportunities for oral interaction existed and to what extent students profited from them. The findings revealed that cooperative learning, which is an important methodology used to enhance student s oral skills, was absent in the classroom. I made recommendations for better exploitation of the opportunities, and learnt myself how to create and exploit opportunities for oral interaction.
: Mémoire
Keywords: Cycle primaire L enseignement de la Langue Anglaise; Elementary Education English Language Education; Nord; North